2010
DOI: 10.1160/th09-12-0837
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and validity of inflammatory biomarkers in the prediction of post-operative atrial fibrillation in coronary artery disease patients

Abstract: Atrial fibrillation (AF) is a common complication of coronary artery bypass grafting (CABG). We sought to determine the diagnostic validity of plasma biomarkers of i) inflammation (marked by interleukin-6 [IL-6] and high-sensitivity C-reactive protein [hs-CRP]), ii) extracellular matrix remodelling (matrix metalloproteinase [MMP-9], tissue inhibitor of matrix metalloproteinase [TIMP-1]) and iii) the prothrombotic state (tissue factor and von Willebrand factor [vWF]) in the risk prediction of post-operative AF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 44 publications
2
42
2
2
Order By: Relevance
“…Although inflammation has been one of the proposed mechanisms of POAF [3,4,5], the results of the present study do not suggest a significant contribution from mediators of the inflammatory response to the risk of this arrhythmia. In fact, our findings contradict the notion that high preoperative levels of inflammatory mediators such as CRP or IL-6 are associated with an increase in the occurrence of POAF in patients undergoing CABG [5].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Although inflammation has been one of the proposed mechanisms of POAF [3,4,5], the results of the present study do not suggest a significant contribution from mediators of the inflammatory response to the risk of this arrhythmia. In fact, our findings contradict the notion that high preoperative levels of inflammatory mediators such as CRP or IL-6 are associated with an increase in the occurrence of POAF in patients undergoing CABG [5].…”
Section: Discussioncontrasting
confidence: 80%
“…The pathophysiology of postoperative AF (POAF) is multifactorial and includes factors related to the surgical procedure as well as the severity of the underlying heart disease and advanced age [2]. The inflammatory reaction induced by the surgery has been implicated as a risk factor for POAF [3,4,5]. The onset of POAF, typically on postoperative day 2, coincides with the peak of C-reactive protein (CRP) elevation and release of the proinflammatory cytokine interleukin-6 (IL-6) [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…49 Marcus and associates, 50 in studying 971 Heart failure is a risk factor for AF Benjamin EJ, et al 40 (1994) Ehrlich JR, et al 41 (2002) No support for a relationship between AF and inflammation -Kallergis EM, et al 37 (2008) Yao SY, et al 36 (2009) AF = atrial fibrillation; Ca = calcium; CRP = C-reactive protein; hs-CRP = high-sensitivity C-reactive protein; LV = left ventricular coronary heart disease participants in the Heart and Soul Study, found that high levels of IL-6 were associated with the risk of AF. Other investigators associated serum IL-6 levels with AF after CABG, 51 after cardioversion, 52 and after radiofrequency catheter ablation. 53 Aviles and associates 22 performed a cross-sectional study of 5,806 subjects and reported that baseline levels of CRP were higher in patients affected by AF even after adjustment for multiple variables potentially associated with AF, and that CRP level is a strong predictor of future AF.…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 99%
“…Although this increasing risk has been attributed primarily to hyperglycaemia, dyslipidemia and a prothrombotic state, recent observations focused on low-grade inflammation in the pathogenesis of type 2 DM and its complications. 23,24 Our study also provided a possible explanation for the apparent paradox that diabetic patients with well-controlled FBG had the similar ECM-related gene expression in SV conduits as uncontrolled diabetic patients. Our data are not with the pathophysiological mechanisms which may be responsible for the different endogenous ECM gene expression levels in diabetic and non-diabetic patients.…”
Section: Discussionmentioning
confidence: 65%